2016
DOI: 10.1039/c6tc02368a
|View full text |Cite
|
Sign up to set email alerts
|

Far- and deep-ultraviolet spectroscopic investigations for titanium dioxide: electronic absorption, Rayleigh scattering, and Raman spectroscopy

Abstract: Various far and deep ultraviolet spectroscopic investigations provide a basic understanding of the properties of TiO2and promising possibilities for its applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 108 publications
0
11
0
1
Order By: Relevance
“…Typical TiO 2 films produced via aerosol-assisted chemical vapor deposition under the conditions used in this study are on the order of a few hundred nanometers thick . The penetration depth of high-energy UV irradiation is commonly estimated within 10–30 nm, although some studies have claimed UV absorption across larger depths. ,, On the basis of literature reports , and the particular physical properties of our films, we estimated an absorption penetration of ca. 17 nm in our case.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Typical TiO 2 films produced via aerosol-assisted chemical vapor deposition under the conditions used in this study are on the order of a few hundred nanometers thick . The penetration depth of high-energy UV irradiation is commonly estimated within 10–30 nm, although some studies have claimed UV absorption across larger depths. ,, On the basis of literature reports , and the particular physical properties of our films, we estimated an absorption penetration of ca. 17 nm in our case.…”
Section: Resultsmentioning
confidence: 96%
“…41 The penetration depth of highenergy UV irradiation is commonly estimated within 10−30 nm, 42 although some studies have claimed UV absorption across larger depths. 16,43,44 On the basis of literature reports 45,46 and the particular physical properties of our films, we estimated an absorption penetration of ca. 17 nm in our case.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported electronic transition spectra in the 140–450 nm region of various ionic liquids by using the attenuated total reflectance (ATR) technique. , In the ATR system, evanescent waves generated at the interface of the ATR prism and a sample were used to probe electronic transition. , In the UV region, the penetration depth, which corresponds to the light path length, is short (<50 nm), thus enabling one to record saturation-free spectra of liquid and solid samples such as water, , organic liquids, , and inorganic semiconductors. In our previous study investigating different ionic liquids (i.e., pyrrolidinium, ammonium, and imidazolium cations with different halide and fluorine-containing anions), electronic transitions that could not be measured by conventional UV–vis spectrometers were observed using ATR. It was revealed that ionic liquids containing pyrrolidinium or ammonium cations and fluorine-containing anions exhibited absorbance only below 200 nm, attributed to electronic transitions solely from the anions.…”
mentioning
confidence: 99%
“…It shows that the absorption between 200 and 300 nm was found to be strong under all the considered conditions of pressurized argon gas and especially at 4 MPa. These absorption peaks were probably caused by titanium oxide nanoparticles that were generated from the titanium-rod electrode consumption during the pulsed discharge experiments. , …”
Section: Results and Discussionmentioning
confidence: 99%